Impact of plasma combustion technology on micro gas turbines using biodiesel fuels - Alrashidi, Ahmed M. R. N.; Adam, Nor Mariah; Mohd Ariffin, Mohd Khairol Anuar; Fnyees, Alajmi; Naser, Alrashidi; Abdul Aziz, Hairuddin (Multidisciplinary Digital Publishing Institute, 2022)
The adoption of biorenewable alternative fuel resources from biofuels (ethanol or biodiesel) has produced promising solutions to reduce some toxic greenhouse gas (GHG) emissions from gas turbine engines (GTEs). Despite the reduced hydrocarbon associated with adopting alternative bio-renewable fuel resources, GTE operations still emit toxic gases due to inefficient engine performance. In this study, we assess the impact of the integration of plasma combustion technology on a micro-GTE using biodiesel fuel from animal fat with the aim of addressing performance, fuel consumption, and GHG emission reduction limitations. Laboratory design, fabrication, assembly, testing, and results evaluation were conducted at Kuwait’s Public Authority for Applied Education and Training. The result indicates the lowest toxic emissions of sulfur, nitrogen oxide (NO), NO2, and CO were from the biodiesel blended fuels. The improved thermal efficiency of GTE biodiesel due to the volume of hydrogen plasma injected improves the engine’s overall combustion efficiency. Hence, this increases the compressor inlet and outlet firing temperature by 13.3 °C and 6.1 °C, respectively. The Plasma technology produced a thrust increment of 0.2 kgf for the highest loading condition, which significantly impacted horsepower and GTE engine efficiency and reduced the cost of fuel consumption.